1
$\begingroup$

We have Cobb-Douglas function like this $Y=AK^\alpha L^{1-\alpha}$, in one of the book, it deduce like this: enter image description here

How can we get this formula? $$\frac{\Delta Y}Y = \frac{\Delta A}A+\alpha\frac{\Delta K}K+(1-\alpha)\frac{\Delta L}L$$

$\endgroup$

1 Answer 1

2
$\begingroup$

Take logs of both sides, i.e. $$\log Y=\log A+ a \log K +(1-a)\log L$$ This gives: $$\Delta\log Y = \Delta\log A + a \Delta\log K +(1-a) \Delta\log L$$

Then use that $\frac{d}{dx}\log x= 1/x$, which yields $\Delta\log x=\Delta x/x$. Apply that to each log-diff above.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.